MODEL BELA NEGARA DALAM PENDIDIKAN KEWARGANEGARAAN PADA PERGURUAN TINGGI MELALUI PROJECT CITIZEN - Suabuana, Cik; Parhan, Muhamad; Chepy, Indra; Fitria, Ratna (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2018)
This study aims to formulate a model of state defense in college students through civic education in order to increase awareness of state defense, in addition to examine how far the model of citizen project in civic education at university towards awareness of society, nation, and state of the student in improving the attitude of the students about the importance of state defense efforts. The research method used is Research Development (R D). Data collection techniques by: questionnaire, observation, test and documentation study. The results showed that the value of t arithmetic t table (8.785 2.023) then Ho is rejected, it means that the method of learning affect the state defense students.